The Influence of Self-Control on Premarital Sexual Behavior - Rahmawati, Aisyah Ayu; Wibowo, Bangun Yoga; Wahyuningsih, Lenny (IAIN Kudus, 2023)
The Influence of Self-Control on Premarital Sexual Behavior. This research aims to determine the effect of self-control on premarital sexual behavior among teenagers in class X at SMAN 1 Bojonegara. The research uses quantitative methods with a correlational type. The population in this study was class X students at SMA Negeri 1 Bojonegara, namely 350 students. Through the probability sampling method and the simple random sampling technique, 188 students were sampled. The data collection method uses a questionnaire, and the measurement scale for self-control and sexual behavior uses a Likert scale. The data analysis technique obtained simple correlation results with a significance value of 0.000<0.05, which means that Ha is accepted and Ho is rejected, so there is an influence between self-control and premarital sexual behavior in adolescents. The correlation value using Karl Pearson's product moment correlation was -0.627, which means that the self-control variable and the premarital sexual behavior variable have a negative relationship, where the higher the self-control, the lower the premarital sexual behavior in adolescents and vice versa.Keywords: Self-Control, Premarital Sexual Behavior, and Adolescents